The liquidity of authentic relationships in the hypermodern era: A study on the fragility of human bonds (Research, Society and Development, 2023)
Introduction: Hypermodernity is a society focused on pleasure and well-being, amplifying the values of modernity, but at the same time, creating a world without references, empty of meaning and purpose. In this context of change, contemporary individualism, changes in intimacy and the fragility of human ties in fluid modernity, are explored, given the changes resulting from socio-relational changes. Objective: the objective of this brief study is to discuss how the sociocultural transformations of hypermodernity impact social representations about commitment and responsibility in human relations. Methodology: narrative literature review through searches in electronic databases SCIELO and CAPES. A search strategy was carried out using the descriptors “hypermodernity”, “Bauman”, “Lipovetsky” and “society”. This study included complete articles available online with approaches on hypermodernity and its impact on commitment and responsibility in Human Relations, published between 2013 and 2023, in Portuguese and English. Articles that were not found in full, published more than ten years ago and/or published in other languages were excluded. Results: the fluidity and flexibility of social relationships have led to a decrease in commitment and responsibility. Conclusion: sociocultural transformations in hypermodernity have radically redefined the dynamics of human relations, undermining the traditional bases of commitment and responsibility.